2016
DOI: 10.1111/aor.12827
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Speed Modulation of a Rotary Total Artificial Heart Impeller

Abstract: Unlike the earlier reciprocating volume displacement-type pumps, rotary blood pumps (RBPs) typically operate at a constant rotational speed and produce continuous outflow. When RBP technology is used in constructing a total artificial heart (TAH), the pressure waveform that the TAH produces is flat, without the rise and fall associated with a normal arterial pulse. Several studies have suggested that pulseless circulation may impair microcirculatory perfusion and the autoregulatory response and may contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
0
23
0
2
Order By: Relevance
“…The CardioSans mock circulatory loop (BiVACOR, Houston, TX, USA), which is capable of simulating vascular pressure, resistance, and compliance of both the pulmonary and systemic circulations, was assembled as described previously (Fig. ; ). A glycerol‐based blood analog is pumped through the system of chambers and reservoirs by the TAH.…”
Section: Methodsmentioning
confidence: 99%
“…The CardioSans mock circulatory loop (BiVACOR, Houston, TX, USA), which is capable of simulating vascular pressure, resistance, and compliance of both the pulmonary and systemic circulations, was assembled as described previously (Fig. ; ). A glycerol‐based blood analog is pumped through the system of chambers and reservoirs by the TAH.…”
Section: Methodsmentioning
confidence: 99%
“…Those who do not use sensors report lower accuracy, according to the literature. [21][22][23][24][25][26][27] The mentioned strategies have been verified in numerical or computational simulations and in vitro tests. Results have been demonstrated that they were able to generate adequate blood flow and pressure.…”
Section: Introductionmentioning
confidence: 97%
“…BiVACOR is an artificial heart created in Houston, Texas, and is currently undergoing animal studies (24). This artificial heart operates by two centrifugal impellers placed on a single magnetically levitated rotor that can provide high flows over 12 L. The pump also has a smart controller that adapts to the changes in the patient's activities.…”
Section: Future Devicesmentioning
confidence: 99%